Combining remotely sensed and survey data to better understand linkages between urbanization and child nutrition: Case study from Burkina Faso - Haile, Beliyou; Guo, Zhe; Arndt, Channing; Ahn, Hee Eun (International Food Policy Research Institute, 2021)
Africa is experiencing a rapid growth in urban population with a billion more people expected to live in cities by 2050. The extent to which urbanization contributes to improvements in the welfare of households and individuals depends on whether it is accompanied by the creation of remunerative employment opportunities and investments on essential infrastructure and services. Specific to child nutrition, urbanization can improve nutrition through its effects on the immediate and underlying determinants that include dietary and nutrient intake, diseases, household food security, environmental sanitation, and access to health services. The direction and strength of the association between urbanization and child undernutrition is therefore an empirical matter that largely depends on the type of urban settlements. This study examines linkages between urbanization and child undernutrition in Burkina Faso. Nutrition data are obtained from the Burkina Faso Demographic and Health Surveys (DHS) con-ducted in 1998/99, 2003, and 2010. Nutritional outcomes of children 0-59 months old are measured using height-for-age z-score (HAZ), weight-for-height z-score (WHZ), and weight-for-age z-score (WAZ). Instead of relying on a binary urban-rural classification available in the DHS data, we construct two continuous indicators of urbanization based on remotely sensed data ‒ the size of urban area within 10 kilometers radius around the DHS cluster (urban extent) and the distance between the child’s DHS cluster and the boundary of the nearest urban settlement (remoteness).